Konsep Kepemimpinan Dari Perspektif Perjanjian Lama: Kisah Daud - Febi Erni Asanab; Rounauly Marbun (Universitas Katolik Widya Karya Malang, 2023)
Leaders are people who can be entrusted with leadership, not just anyone, but people who really have a leadership spirit because we can see from Bible figures in the Old Testament like